Gendered perspectives on conflict and violence - Segal, Marcia Texler, 1940-; Demos, Vasilikie P. (Bingley, U.K. : Emerald, 2013)
The chapters in this two-part volume deal with a range of gender-based violence issues that are making news headlines daily. In Part A the contributors address the ways in which wartime rape is treated in international courts, why and how the gender language used at the United Nations matters, how asylum-seekers fleeing gendered violence are treated, how the press and the courts frame rape and other acts of violence, perceptions and responses of and to disabled and LGBTQ people who are victims of gendered violence, the ways we respond to the perpetrators of violence, and the relationship of military service to nationalism. The focus of the volume is global in the sense that international law and tribunals are discussed and norms and attitudes from global samples are compared. A variety of qualitative and quantitative methods including interviews, textual analysis, autoethnography, and secondary analysis of large sample surveys are employed. Each of the chapters has theoretical as well as policy or social implications.
Gendered perspectives on conflict and violence : an introduction / Vasilikie Demos, Marcia Texler Segal -- Victimized again? Intersectionality and injustice in disabled womens lives after hate crime and rape / Susie Balderston -- Feminist reflections on disability hate crime / Mark Sherry -- Intimate partner violence among self-identified queer victims : towards an intersectional awareness in scholarship and organizing surrounding gender-based violence / Avery Everhart, Gwen Hunnicutt -- In letting the perpetrator speak : sexual violence and classroom politics / Jane Kilby -- Invisible lives, silenced violence : transphobic gender violence in global perspective / Daniela Jauk -- Belonging to the Jewish nation : life stories of Israeli female combat soldiers / Channa Zaccai -- Private war, private suffering, and the normalizing power of law / Bianca Baggiarini -- Significance of wartime rape / Caterine Arrabal Ward -- Out of southeast Europe : gender-based violence, public transitions, and the search for home / Susan C. Pearce -- Layers of violence : a gender perspective on media reporting on infant rape in South Africa / Jessica Dutton -- Gender equality, attitudes to gender equality, and conflict / ôsa Ekvall.
Print version record
Keywords: Social Science -- Gender Studies; Social Science -- General; Social Science -- Feminism & Feminist Theory; "Gender studies, gender groups".; Sociology; Women -- Abuse of; Family violence; Gender identity